A consumer's eye view of family-involved alcohol treatment. Issue 1 (2nd January 2019) - McCrady, Barbara S.; Wilson, Adam; Fink, Brandi; Borders, Adrienne; Muñoz, Rosa; Fokas, Kathryn
ABSTRACT: Family involvement leads to better outcomes of alcohol treatment, but empirically-supported family treatments have not been adopted widely. The current study obtained consumer perspectives to inform development of a family treatment designed to be adopted by community programs. Four focus groups (N=25; 6 patients, 4 family members, 15 clinicians) were analyzed based on a coding system developed using Grounded Theory. Patient alcohol use negatively impacted family interactions, relationships, and resources. Family involvement barriers included: pragmatic challenges, institutional barriers, and family/patient ambivalence. Strategies to increase family involvement included: enhancing positive interactions, maintaining optimism about family involvement, and clinicians recommending family involvement.